Implementasi Pendidikan Akhlak di Pondok Pesantren Studi Pada Lembaga Pendidikan Pondok Pesantren Tazkiyatunnufus - Edy, Edy; Hadawiyah, Robiatul; Burhanudin, Ohan (STIT Sirojul Falah Bogor, 2022)
Moral education is an important aspect in educational purpose. It is related to the increasing and varied phenomenon of moral decadence that occurs in our society and in government circles. Moral education is the right answer to these problems and Islamic boarding schools are a place for Islamic religious education, especially to build a good character and moral values in children. In Islamic teachings, moral education is a process of shaping good morals, personality and character, who is responsible for the tasks that Allah has given in order to carry out His commands and obey His prohibitions. In this study the authors conducted a study at a boarding school located in Cibinong, Kab. Bogor which named Tazkiyatunnufus Islamic boarding school. This study aims to determine the effectiveness of the implementation of moral education for students at the Tazkiyatunnufus Islamic boarding school and to understand the various processes of implementing moral education in the Tazkiyatunnufus Islamic boarding school. The method used in this research is a qualitative method of the type of field study (field study). The process of implementing moral education at the Tazkiyatunnufus Islamic boarding school uses a variety of methods, namely through diniyah, story telling, muthola’ah, giving good examples, and through reward and punishment. Keywords: Moral education, Islamic boarding school.